2014
DOI: 10.1016/j.diii.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Peptide receptor radionuclide therapy of neuroendocrine tumors with 90Y-DOTATOC: Is treatment response predictable by pre-therapeutic uptake of 68Ga-DOTATOC?

Abstract: Pre-therapeutic (68)Ga-DOTATOC tumor uptake as well as assumed uptake of (90)Y-DOTATOC are strongly associated with the results of subsequent PRRT. The defined cut-off values should be confirmed by prospective studies and may then provide the rationale for individual dosing and selecting patients with high likelihood of favorable treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 38 publications
2
42
2
2
Order By: Relevance
“…Early prediction of treatment response is essential to guide tumor therapy and avoid unnecessary side effects and costs from ineffective treatments. SUV has been proposed as a marker of SSTR density but changes of tumor SUV at 68 Ga-DOTATOC PET/CT during PRRT have not been found to reliably correlate with the patient outcome (24,27,(41)(42)(43). It was previously shown that K i and SUV are not linearly correlated for NETs (especially for higher SUVs .…”
Section: Discussionmentioning
confidence: 99%
“…Early prediction of treatment response is essential to guide tumor therapy and avoid unnecessary side effects and costs from ineffective treatments. SUV has been proposed as a marker of SSTR density but changes of tumor SUV at 68 Ga-DOTATOC PET/CT during PRRT have not been found to reliably correlate with the patient outcome (24,27,(41)(42)(43). It was previously shown that K i and SUV are not linearly correlated for NETs (especially for higher SUVs .…”
Section: Discussionmentioning
confidence: 99%
“…Für die Empfehlung zur PRRT wurde daher ein Tumor-Uptake über dem normalen Leberuptake empfohlen. Für die Ga-68 DOTA-TOC-PET/CT wurde gezeigt, dass der Therapieerfolg mit der Höhe des maximalen prätherapeutischen Standardized Uptake Value (SUVmax) korreliert [578].…”
Section: Empfehlung Konsensunclassified
“…Similar to the current study's data, Gabriel et al (18) did not find any relationship between tumor response and SUVs of Ga-68 DOTATATE PET/CT. However, recently Oksüz et al (19) showed a correlation in SUVs of reference lesions and treatment response with a cutoff value of 17.9. Differing from the current study, a mixed response classification and different time period were used for Ga-68 DOTATOC imaging.…”
Section: Treatment Responsementioning
confidence: 99%